Remediation of polluted river water by biological contact oxidation process using two types of carriers - Wu, Weizhong; Yong Liu; Zhu, Qing; Wei, Caijie; Wang, Jianlong (INTERNATIONAL JOURNAL OF ENVIRONMENT AND POLLUTION, 2009)
Biological contact oxidation technology was used to remediate the polluted river water in Hanyang, China. The purification effect of the polluted river water in three simulated rivers was investigated using two different carriers, i.e., AquaMats made in USA and semi flexible supports made in China. The results showed that when the hydraulic loading rate increased, purification effect in terms of COD(Mn) decreased. Moreover, the removal efficiency of total nitrogen (TN) increased when AquaMats support was used, however it decreased when semi flexible support was used, in comparison with the control experiment. The removal ability of total phosphorus (TP) was strengthened by using different carriers.